Model Pembelajaran Talking Stick sebagai Sarana Peningkatan Hasil Belajar Fiqh Siswa Kelas IV - Maftuhin Maftuhin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
Fiqh learning is an integral part of the Islamic Religious Education subject which aims to provide students with an understanding of Islamic teachings, especially in terms of sharia law, and to guide them in forming beliefs and understanding Islamic law correctly. However, the implementation of Fiqh learning which is still dominated by a teacher-centered approach tends to cause low active student participation. In addition, the use of conventional lecture methods creates a monotonous impression which has an impact on low learning outcomes. This study aims to determine the effectiveness of the application of the Talking Stick learning model in improving the learning outcomes of fourth grade students at MI Ma’arif Sidasari. This study uses the Classroom Action Research (CAR) method which is carried out in three stages, namely pre-cycle, cycle I, and cycle II. The results of the study showed an increase in learning outcomes, with an average student score in cycle I of 73.2 which then increased to 83.5 in cycle II. The percentage of student learning completion also increased significantly. Thus, it can be concluded that the application of the Talking Stick learning model is effective in improving student learning outcomes in the Fiqh subject in fourth grade MI Maarif Sidasari.